2011
DOI: 10.1007/s10753-011-9343-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of Elaeocarpus petiolatus Inhibits Lipopolysaccharide-Induced Inflammation in Macrophage Cells

Abstract: Elaeocarpus petiolatus is known to exert active oxygen scavenging, anti-aging, and whitening actions. However, the biological effects of E. petiolatus on inflammation and the underlying mechanisms are yet to be established. In the present study, we investigated the anti-inflammatory effects of the ethanol extract from E. petiolatus (EPE) bark in murine Raw264.7 macrophages stimulated with lipopolysaccharide (LPS). EPE inhibited the production of PGE(2), TNF-α, and IL-1β in a dose-dependent manner in Raw264.7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…These findings are in agreement with previous studies that reported that WFRG promotes the proliferation of macrophages in vitro (19), and that the proliferation of macrophages enhances immune activity (20). For this reason, a concentration of 100 μg WFRG/mL was used in all subsequent experiments.…”
Section: Resultssupporting
confidence: 93%
“…These findings are in agreement with previous studies that reported that WFRG promotes the proliferation of macrophages in vitro (19), and that the proliferation of macrophages enhances immune activity (20). For this reason, a concentration of 100 μg WFRG/mL was used in all subsequent experiments.…”
Section: Resultssupporting
confidence: 93%
“…5E). COX-2 is also a key driver of inflammation whose expression is enhanced by proinflammatory cytokines (18). COX-2 was markedly upregulated in the livers of rabbits with RHDV infection, and this effect was significantly reduced by CT-1 (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Our data indicate that the beneficial effect of CT-1 appears to be due to the mitigation of inflammation, the reduction of oxidative stress, and the activation of endogenous cytoprotective and growth-promoting mechanisms. Indeed, CT-1-treated animals exhibited a significant reduction in the expression of key drivers of inflammation, such as TNF-␣, IL-1␤, COX-2, and TLR4, which are known to be relevant mediators of tissue damage in the inflamed liver (2,10,18). On the other hand, in the treated rabbits the alleviation of the inflammatory reaction within the liver was accompanied by a significant decrease in oxidative stress as reflected by decreased levels of lipid peroxidation products and reduced GSSG/GSH ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS stimulation of macrophages (RAW264.7) is a widely used in vitro model for evaluating the potency of anti-inflammatory drugs and exploring their mechanisms of action30. LPS can activate several extracellular signaling pathways, including NF-κB and MAPKs2831.…”
Section: Discussionmentioning
confidence: 99%